A GARCH analysis of the holiday effect in the South African equity market: Array - Mazviona, Batsirai; Mah, Gisele; Choga, Ireen (Acta Universitatis Danubius. Œconomica, 2021)
Holiday effect are part of seasonal anomalies pronounced in financial markets and are attractive to technical traders who employ past information generated from trading activities to device profitable strategies. The aim of this article is to assess the holiday anomaly on the South African equity market. Financial data for Johannesburg Stock Exchange (JSE) indices covers the period 1995-2018. Ten JSE indices namely Top 40, All Shares, Basic Materials, Industrials, Consumer Goods, Health Care, Consumer Services, Telecommunications, Financials and Technology were analysed. The holiday effect was modelled by Generalized Auto Regressive Conditional Heteroskedasticity Model (GARCH), exponential GARCH (EGARCH) and threshold GARCH (TGARCH) models. The GARCH models were estimated in Eviews with R integration. No pre-holiday effect was found in both aggregate and sectoral indices of the mean equation. However, a negative pre-holiday effect for aggregate indices, namely the Top 40 and All Shares, and the sectoral indices of Basic materials, Industrials, Consumer goods, Health care, Consumer services, Telecommunications, Financials and Technology was observed in the variance equation. The mean equation unveiled a post-holiday effect in the aggregate indices, that is the Top 40 and All Shares, as well as the Basic materials, Industrials, Consumer goods, Health care, Consumer services, Telecommunications, Financials, and Technology sectors. The variance equation showed a positive post-holiday effect in the Top 40 and All Shares indices, together with the Basic materials, Industrials, Consumer goods, Health care, Consumer services, and Financials sectors. Investors should avoid investing in the Basic materials sector as it increases their exposure. The pre-holiday trading strategy is useful in reducing investors’ risk exposure through investing in the Basic materials sector. When it comes to post-holiday seasonal trading, it is recommended that investors focus on the Telecommunications sector to earn excess returns. Investors can avoid making losses by ignoring the Industrials sector, since it has the effect of increasing risk exposure. Our study delineates holiday anomaly for key sectorial indices in South African equity as opposed to past empirical studies that focus on aggregate indices.